Bilateral Ear Swelling and Erythema after Chemotherapy: A Case Report of Ara-C Ears - Pitchaya Jaruvijitrattana; Kumutnart Chanprapaph (Karger Publishers, 2019)
Cytarabine is an antimetabolite commonly used to treat hematological malignancies, especially acute myeloid leukemia (AML), acute lymphoblastic leukemia, and non-Hodgkin's lymphoma. Cytarabine-induced cutaneous adverse effects are common, usually manifesting as morbilliform eruptions predominantly on the acral site, intertriginous zone, and to a lesser extent on the elbows, knees, neck, and ears. The presentation on ears is usually called "Ara-C ears," which is considered as a rare subtype of acral erythema. We report a 53-year-old Thai woman with AML who developed cytarabine-induced rashes. The lesions began on symmetrical bilateral ears, posterior auricular areas, and forehead followed by expansion to the trunk and extremities. The clinical presentations and histopathological findings were compatible with toxic erythema of chemotherapy. After giving cetirizine 10 mg orally twice daily and 0.1% triamcinolone acetonide cream twice daily, the lesions gradually improved over 10 days. Notably, two additional courses of high-dose cytarabine were administered without any recurrence.